The Influence of Body Image on Self-Confidence in Secondary School Students and Its Implications - Sintya Nuraini; Nurul Fajri; Rosada` Rosada (Asosiasi Asesmen Pendidikan, 2026)
This study aims to examine the influence of Body Image on Self Confidenceamong students at Madrasah Tsanawiyah Negeri 2 Jakarta. Using a quantitative descriptive approach with simple linear regression analysis, data were collected from 111 eighth-grade students through questionnaires measuring Body Image and self-confidence. The results showed a significant positive relationship between Body Image and Self Confidence(p < 0.05), with a regression coefficient of 0.789 and an R² value of 0.493. This indicates that 49.3% of the variation in Self Confidenceis influenced by Body Image. The findings suggest that students with a more positive Body Image tend to have higher levels of self-confidence. The study highlights the importance of implementing guidance and counseling services in schools to support students' personal development, particularly in strengthening Self Confidencethrough Body Image awareness.